Analisis Kinerja Karyawan Berdasarkan SOP Penerimaan Material yang Berlaku di PT Prima Karya Teknik dengan Metode KPI (Key Performace Indicator) - Rozak, Fatkhur; Riyana, Iis (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
PT Prima Karya Teknik is a company engaged in construction and fabrication, where the material receiving process is a critical stage that affects project smoothness, operational costs, and customer satisfaction. However, the company faces several problems in the material receiving process, such as delays in material inspection, document discrepancies, and lack of team coordination, which are thought to be related to employee performance that has not been optimal in carrying out the SOP. This study aims to analyze employee performance based on the Standard Operating Procedure (SOP) for material acceptance that applies at PT Prima Karya Teknik using the Key Performance Indicator (KPI) method. The results of the analysis show that there are several areas that need to be improved such as material receipt time that still exceeds the target, material receipt accuracy that has not reached the standard and the timeliness of receipt that still needs to be improved. Based on these findings, several improvements are suggested such as implementing a barcode system, retraining employees regarding SOPs, rearranging work shifts, and improving coordination with suppliers.